Meningkatkan Motivasi Belajar Siswa Melalui Pemberian Reward dan Punisment bagi Siswa Madrasah Tsanawiyah - Ahmad Ahmad; Parihin Parihin; Halimatuzzahrah Halimatuzzahrah; Miftahul Jannah; Ria Rismayati; Suriyati Suriyati (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
The purpose of this study is to find out how students' motivation after being given Reward and Punishment, Kedalan faced and solutions to obstacles faced when given Reward and Punishment for Grade VIII MTs Students Nurul Yaqin Kelanjur. This research was designed with a cauldronative research method with descriptive characteristics. Qualitative research is research that produces descriptive data in the form of written or spoken words from people and behavior that can be observed. The data collection method used is observation method, interview, and documentation. Data analysis methods are inductive with data reduction preparation, data display, and inference preparation steps. The results of this study showed that rewarding and punishment in grade VIII MTs Nurul Yaqin Kelanjur has a positive influence on students' learning motivation. The form of reward applied in Class VIII MTs Nurul Yaqin Kelanjur is a reward in the form of material and non-material. Reward in non-material form in the form of praise, support, appreciation, and so forth. While the reward in the form of material in the form of giving books, certificates, trophies, scholarships, and so forth. While the form of punsihment applied is punishment in the form of speech, such as criticism, scorn, bentakan and threats. Punishment in physical form is rarely done, except in very forceful circumstances and no other punishment is used to change the student's behavior in a better direction. Reward and punishment in MTs Nurul Yaqin Kelanjur encountered various problems that can cause the application of reward and punishment to be less effective. However, by working with parents, teachers and principals can overcome various problems, so that the application of reward and punishment can be carried out effectively in increasing student learning motivation.